Targeting the Endocannabinoid System for Prevention or Treatment of Chemotherapy-Induced Neuropathic Pain: Studies in Animal Models - Willias Masocha (Pain Research and Management)
There is a scarcity of drugs to either prevent or properly manage chemotherapy-induced neuropathic pain (CINP). Cannabis or cannabinoids have been reported to improve pain measures in patients with neuropathic pain. For this review, a search was done in PubMed for papers that examined the expression of and/or evaluated the use of cannabinoids or drugs that prevent or treat established CINP in a CB receptor-dependent manner in animal models. Twenty-eight articles that fulfilled the inclusion and exclusion criteria established were analysed. Studies suggest there is a specific deficiency of endocannabinoids in the periphery during CINP. Inhibitors of FAAH and MGL, enzymes that degrade the endocannabinoids, CB receptor agonists, desipramine, and coadministered indomethacin plus minocycline were found to either prevent the development and/or attenuate established CINP in a CB receptor-dependent manner. The studies analysed suggest that targeting the endocannabinoid system for prevention and treatment of CINP is a plausible therapeutic option. Almost 90% of the studies on animal models of CINP analysed utilised male rodents. Taking into consideration clinical and experimental findings that show gender differences in the mechanisms involved in pain including CINP and in response to analgesics, it is imperative that future studies on CINP utilise more female models.